[Passport fixing 2 ; Blanco, Jose ; Generics [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Discusses the passport irregularities that happened in the Department of Foreign Affairs ; interview with Pitok, an artist about his work and family ; Senate Bill 453 requiring all doctors to prescribe generic drugs.